The Bacterial Genomic Context of Highly Trimethoprim-Resistant DfrB Dihydrofolate Reductases Highlights an Emerging Threat to Public Health - Claudèle Lemay-; Sarah-Slim Diwan; Joelle N. Pelletier (MDPI AG, 2021)
Type B dihydrofolate reductase (dfrb) genes were identified following the introduction of trimethoprim in the 1960s. Although they intrinsically confer resistance to trimethoprim (TMP) that is orders of magnitude greater than through other mechanisms, the distribution and prevalence of these short (237 bp) genes is unknown. Indeed, this knowledge has been hampered by systematic biases in search methodologies. Here, we investigate the genomic context of dfrbs to gain information on their current distribution in bacterial genomes. Upon searching publicly available databases, we identified 61 sequences containing dfrbs within an analyzable genomic context. The majority (70%) of those sequences also harbor virulence genes and 97% of the dfrbs are found near a mobile genetic element, representing a potential risk for antibiotic resistance genes. We further identified and confirmed the TMP-resistant phenotype of two new members of the family, dfrb10 and dfrb11. Dfrbs are found both in Betaproteobacteria and Gammaproteobacteria, a majority (59%) being in Pseudomonas aeruginosa. Previously labelled as strictly plasmid-borne, we found 69% of dfrbs in the chromosome of pathogenic bacteria. Our results demonstrate that the intrinsically TMP-resistant dfrbs are a potential emerging threat to public health and justify closer surveillance of these genes.